Decorative floral plants in the urban flora structure of the Forest-Steppe zone of Ukraine - Марченко, А. Б. (Scientific Progress & Innovations, 2016)
According to the results of monitoring of the floristic diversity of ornamental floral plants in the structure of urban ecosystems’ greenery of Forest-Steppe zone of Ukraine we have clarified their taxonomic composition. Decorative floral plants in the structure of urban flora are presented by 118 species from 58 genera 31 families 16 orders of 2 classes. Dicotyledones class dominates in terms of quantity, representing 66,1 %, and the Liliopsida class represents 33,9 % of species. Dicotyledones class numbers 14 orders, in which Asteralesorder occupies a dominant place on the number of species (34 % of species), other orders of Saxifragales Dumort are represented by 13 %, Brassicales Bromhead – by 8,9 %, Ericales – by 7,6 %, Lamiales Bromhead, Rosales – by 6,4 %. Other orders are represented by 1–2 species. Liliopsida class is represented by two orders, among which Asparagales Bromhead dominates in terms of the number of species (70 %). According to the classification by I. G. Serebryakov, decorative floral plants are represented with herbal terrestrial plants (98,8 %), tree life forms (1,2 %), which are represented with monocarpic (71 %) and polycarpic herbs (27,8 % ), shrubs (1,2 %). According to the classification by H. Raunkiyer, decorative floral crops are represented by the following forms: therophytes (71 %), cryptophytes (27,8 %), tall aerial plants (1,2 %). According to all environmental indicators, in terms of moisture, all terrestrial plants are divided into mesophytes (52 %), xeromesophytes (24 %), xerophytes (21 %), mesohygrophytes (3 %); in terms of light intensity – heliophytes (81 %), sciophytes (19 %).